Integrative science a modeling challenge. - Coatrieux, J.L.
Computational modeling and information technology in biology and medicine will play a major role in the interdisciplinary attempt to elucidate structures and functions of living systems. The recursion between organization levels, at all space and time scales, for highly dynamical, interacting, and complex systems (i.e., the integrative science) is a very challenging topic where formal models, observational tools, and experimental investigations have to be closely designed and confronted together. This first in a series of short articles will examine some of the issues to deal with and enhance the perspectives that can be expected from the coupling between modeling and processing frames.
Keywords: Biology; Biomedical technologies; Cellular levels; Complex data fluctuations; Complex systems; Computational modeling; Information technology; Integrative science; Living systems; Medicine; Multimodal image processing; Multimodal signal processing